Etnografi Komunikasi Dalam Tradisi Makan Sinonggi Pada Masyarakat Tolaki Sulawesi Tenggara - ., Sultrayansa; Lestari, Dian Trianita (CV. ITTC INDONESIA, 2026)
Culinary traditions are an important part of culture because they not only meet biological needs but also serve as a medium of cultural communication with deep social meaning. Sinonggi, a Tolaki-style dish, is one of the traditional foods with strong symbolic value in Southeast Sulawesi. The problem in this study is how the Sinonggi eating tradition contributes to the preservation and communication of the Tolaki people's cultural identity in the face of modernization and lifestyle changes. This study examines communication patterns, symbolic meanings, and cultural values associated with the Sinonggi eating tradition. This study aims to understand Sinonggi as a cultural communication medium that represents the values of togetherness, solidarity, and local wisdom among the Tolaki people. The research method used is a qualitative research method with an ethnographic communication approach, based on observations of Sinonggi's practice of eating together in the Tolaki community. This study's theoretical framework is based on Dell Hymes' concept of communication ethnography, specifically the SPEAKING model, as well as the view of culture as a meaning system. The findings indicate that Sinonggi serves as a symbol of unity and a form of nonverbal communication that strengthens social relations within the Tolaki community and across cultures. Sinonggi's communal eating tradition promotes mutual cooperation, simplicity, and respect. Sinonggi is a traditional food and cultural communication tool for the Tolaki people in Southeast Sulawesi, helping to preserve their identity and social values